Spotting Signs of Autism in 3-Year-Olds: Comparing Information from Parents and Preschool Staff - Nilsson Jobs, E.; Bolte, Sven; Falck-Ytter, T. (Springer New York LLC, 2018)
© 2018, The Author(s). Preschool informants may provide valuable information about symptoms of autism spectrum disorder (ASD) in young children. We compared the diagnostic accuracy of ratings by preschool staff with those by parents of 3-year-old children using the Achenbach System of Empirically Based Assessment Preschool Forms. The sample consisted of 32 children at familial risk for ASD without diagnosis, 10 children at risk for ASD with diagnosis, and 14 low-risk typically developing controls. Preschool staff ratings were more accurate than parent ratings at differentiating children with and without ASD, and more closely associated with clinician-rated symptoms. These results point to the value of information from preschool informants in early detection and diagnostic assessments.